Severity of Intimate Partner Violence and Emotional Reactions in Women - Méndez Sánchez, María del Pilar (Consorcio de Universidades Mexicanas A.C., 2022)
Intimate partner violence is one of the most common forms of violence against women, it includes physical, psychological, sexual, economic and social violence. Intimate partner violence causes physical and mental health problems, like depression and anxiety, being the most vulnerable women those who have low schooling, have been exposed to child abuse and have experience of family violence. Based on the literature, a quantitative study was carried out with a parametric correlational design, with a sample obtained in a non-probabilistic way. The objective of this research was to analyze the influence of intimate partner violence in the presence of emotional reactions in women; also, the severity of violence was analyzed. 236 women participated with a mean age of 36.36 years (SD = 8.90), the Emotional Responses to Violence Questionnaire and the Scale of Violence were used. The results indicated positive correlations between violence and emotional reactions, while in the structural equations path model it was observed that violence influences emotional reactions: psychological violence in depression and irritable mood, sexual violence in anxiety and adjustment psychosocial, and physical violence in anxiety. Finally, it is reported that women with less schooling, married women and housewives perceive more violence. It is found that most women do not suffer severe violence, however, if they perceive it, they report psychological violence first, followed by physical and sexual violence.